Applications and challenges in using LC–MS/MS assays for quantitative doping analysis. (June 2016) - Wang, Zhanliang; Lu, Jianghai; Zhang, Yinong; Tian, Ye; Yuan, Hong; Xu, Youxuan
LC–MS/MS is useful for qualitative and quantitative analysis of 'doped' biological samples from athletes. LC–MS/MS-based assays at low-mass resolution allow fast and sensitive screening and quantification of targeted analytes that are based on preselected diagnostic precursor–product ion pairs. Whereas LC coupled with high-resolution/high-accuracy MS can be used for identification and quantification, both have advantages and challenges for routine analysis. Here, we review the literature regarding various quantification methods for measuring prohibited substances in athletes as they pertain to World Anti-Doping Agency regulations.